Why do parents willingness-to-pay to vaccinate their children against COVID-19? A real-world evidence in Taizhou, China - Tao-Hsin Tung; Xiao-Qing Lin; Yan Chen; Hongwei Wu; Mei-Xian Zhang; Jian-Sheng Zhu (Taylor & Francis Group, 2022)
Purpose This population-based cross-sectional study was conducted to explore whether parents are willing to pay to vaccinate their children against COVID-19 in China. Methods With a self-administered online questionnaire, we investigated parents' willingness to pay for their children to be vaccinated against COVID-19 in Taizhou, China. Of the 1,845 parents who answered the structured questionnaire when they received an e-mail or e-poster invitation, 1788 samples with valid data underwent data analysis. Results A total of 66.1% of parents reported being willing to pay to inoculate their children with the COVID-19 vaccine. After adjustment for confounding factors, lower education level, one-child family (yes vs. no, OR = 1.35, 95%CI: 1.04-1.74), knowledge score of vaccination against COVID-19 (high vs. low, OR = 1.31, 95%CI: 1.01-1.69), awareness of the permitted use of the vaccine (yes vs. no, OR = 1.51, 95%CI: 1.16-1.97), and willingness to pay for a COVID-19 vaccine for themselves (yes vs. no, OR = 16.31, 95%CI: 12.59-21.14) were significantly associated with parents' willingness to pay for their children. Conclusion We found that a moderate proportion of parents reported unwillingness to pay for their child to be vaccinated against COVID-19. The results indicate that further detailed assessment and more health education planning are required to increasing parents' WTP for the vaccination of children in China.